Uji Beban Statis Dan Dinamis Jembatan Baja Komposit Batang Toru-4 - Khoeri, Heri; Nugroho, Panji (Civil Engineering Department, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
Bridges are vital infrastructure that require feasibility evaluation before being used to ensure user safety. Feasibility assessment can be done through dynamic and static tests. The dynamic parameters used are natural frequency and damping ratio, while static parameters include deflection and strain during loading. This study conducted forced vibration tests and static load tests on the Batang Toru-4 Bridge. The vibration test results showed a natural frequency of 3,248 Hz, lower than the minimum limit of 3,357 Hz according to Bina Marga empirical data, but still above the British Standard, and a damping ratio of 7.636%, indicating an indication of excessive energy dissipation which is generally due to defects in the structure. However, the static test showed a maximum deflection at 100% UDL of 11.9 mm, still far below the permissible limit of 50 mm. The residual deflection ratio was also only 0.044, still below the permissible limit of 0.2. Therefore, with these results, the bridge was declared functionally fit, but it was recommended to conduct further checks to ensure that excessive damping was not caused by structural damage. The calculated relative capacity is approached by a more conservative dynamic load test compared to a static load test, so that the dynamic load test is an alternative test with a relatively faster time, easier and more conservative results compared to the static load test.